Problematika Orang Tua dalam Mengembangkan Kemampuan Menghafal Al-Qur’an Bagi Anak di Desa Bogor Baru Kecamatan Kepahiang Kabupaten Kepahiang - Intan Permata Sari; Zulkarnain; Adi Saputra (Yayasan Darussalam Bengkulu, 2024)
The researcher raised the issue of: The Problems of Parents in Developing the Ability to Memorize the Al-Qur'an for Children in Bogor Baru Village, Kepahiang District, Kepahiang Regency. This type of research is a descriptive research using a qualitative approach. There were 12 research informants with purposive sampling technique. Data collection techniques are observation, interviews, and documentation. Data analysis uses the concept of Miles and Huberaman, data analysis is carried out interactively and continues until it is complete so that the data is saturated with the stages of data reduction, data presentation, and finally conclusions. The results of this study indicate that the problem of parents in developing the ability to memorize the Al-Qur'an for children in Bogor Baru Village, Kepahiang District, Kepahiang Regency is caused by two factors, namely internal and external factors. From within, such as: feeling lazy to memorize, not fluent in memorizing the Qur'an, often forgetting verses, from external factors not being able to divide time well, the influence of cellphones because playing cellphones continuously is also a problem in children in memorizing Al -Qur'an. The solution to the problem of memorizing the Qur'an for children in Bogor Baru Village, Kepahiang District, Kepahiang Regency, for the existing problems, there is a solution so that memorizing the Qur'an becomes smooth and good. The feeling of laziness and boredom in children must be motivated or can be rewarded for memorizing so that children are eager to memorize, problems are not fluent in memorizing the Qur'an, children are given tutoring with patience and do not scold children, often forget the verse, children do muraja'ah so that reading is maintained and to divide time and the influence of cellphones, parents supervise every activity of children.